Sensitization and Desensitization in Vascularized Composite Allotransplantation - Moris, Dimitrios; Cendales, Linda C. (Frontiers in Immunology, 2021)
Vascularized composite allotransplantation (VCA) is a field under research and has emerged as an alternative option for the repair of severe disfiguring defects that result from severe tissue loss in a selected group of patients. Lifelong immunosuppressive therapy, immunosuppression associated complications, and the effects of the host immune response in the graft are major concerns in this type of quality of life transplant. The initial management of extensive soft tissue injury can lead to the development of anti-HLA antibodies through injury-related factors, transfusion and cadaveric grafting. The role of antibody-mediated rejection, donor-specific antibody (DSA) formation and graft rejection in the context of VCA still remain poorly understood. The most common antigenic target of preexisting alloantibodies are MHC mismatches, though recognition of ABO incompatible antigens, minor histocompatibility complexes and endothelial cells has also been shown to contribute to rejection. Mechanistically, alloantibody-mediated tissue damage occurs primarily through complement fixation as well as through antibody-dependent cellular toxicity. If DSA exist, activation of complement and coagulation cascades can result in vascular thrombosis and infarction and thus rejection and graft loss. Both preexisting DSA but especially de-novo DSA are currently considered as main contributors to late allograft injury and graft failure. Desensitization protocols are currently being developed for VCA, mainly including removal of alloantibodies whereas treatment of established antibody-mediated rejection is achieved through high dose intravenous immunoglobulins. The long-term efficacy of such therapies in sensitized VCA recipients is currently unknown. The current evidence base for sensitizing events and outcomes in reconstructive transplantation is limited. However, current data show that VCA transplantation has been performed in the setting of HLA-sensitization.